In Vivo Efficacy of Umbilical Cord Blood Stem Cell-Derived NK Cells in the Treatment of Metastatic Colorectal Cancer - Veluchamy, John P.; Lopez-Lastra, Silvia; Spanholtz, Jan; Bohme, Fenna; Kok, Nina; Heideman, Daniëlle A. M.; Verheul, Henk M. W.; Di Santo, James P.; de Gruijl, Tanja D.; van der Vliet, Hans J. (Frontiers in Immunology, 2017)
Therapeutic monoclonal antibodies (mAbs) against the epidermal growth factor receptor (EGFR) act by inhibiting EGFR downstream signaling and by eliciting an NK cell-mediated anti-tumor response. The IgG1 mAb cetuximab has been used for treatment of RASwt metastatic colorectal cancer (mCRC) patients, showing limited efficacy. In the present study we address the potential of adoptive NK cell therapy to overcome these limitations investigating two allogeneic NK cell products, i.e. activated peripheral blood NK cells (A-PBNK) and umbilical cord blood stem cell derived NK cells (UCB-NK). While cetuximab monotherapy was not effective against EGFR- RASwt, EGFR+ RASmut and EGFR+ BRAFmut cells, A-PBNK were able to initiate lysis of EGFR+ colon cancer cells irrespective of RAS or BRAF status. Cytotoxic effects of A-PBNK (but not UCB-NK) were further potentiated significantly by coating EGFR+ colon cancer cells with cetuximab. Of note, a significantly higher cytotoxicity was induced by UCB-NK in EGFR-RASwt (42 ± 8% versus 67 ± 7%), EGFR+ RASmut (20 ± 2% versus 37 ± 6%) and EGFR+ BRAFmut (23 ± 3% versus 43 ± 7%) colon cancer cells compared to A-PBNK and equaled the cytotoxic efficacy of the combination of A-PBNK and cetuximab. The anti-tumor efficacy of UCB-NK cells against cetuximab resistant human EGFR+ RASmut colon cancer cells was further confirmed in an in vivo preclinical mouse model where UCB-NK showed enhanced anti-tumor cytotoxicity against colon cancer independent of EGFR and RAS status. As UCB-NK have been proven safe in a recently conducted phase I clinical trial in acute myeloid leukemia, a fast translation into clinical proof of concept for mCRC could be considered.